2013
DOI: 10.1111/j.1600-0706.2013.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in prey consumption of centipede predators in forest soils as indicated by molecular gut content analysis

Abstract: Predation is an important ecological factor driving animal population structures, community assemblages and consequently ecosystem stability and biodiversity. Many environmental factors influence direction and intensity of predation, suggesting that trophic linkages between animals vary between different habitats. This in consequence has particular relevance in anthropogenically altered habitats such as managed forests, where disturbance regime, tree composition and stand age may change the natural food web st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…Overall, we found only few effects of the land‐use types on food‐web topology. Most of these effects could readily be assigned to the dominant tree species that cause different litter types (needles vs leaf litter) and habitat structures (Ferlian and Scheu , Günther et al ). This suggests that the structure of soil food webs is relatively robust against variation in forest types.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we found only few effects of the land‐use types on food‐web topology. Most of these effects could readily be assigned to the dominant tree species that cause different litter types (needles vs leaf litter) and habitat structures (Ferlian and Scheu , Günther et al ). This suggests that the structure of soil food webs is relatively robust against variation in forest types.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, closely related species of lithobiids and geophilomorphs have been found to be trophically distinct with trophic niches in lithobiid species even varying between life stages presumably due to the ability of larger individuals to catch large mobile prey (Ferlian et al ). Using molecular gut content analysis, Günther et al () also found that Lithobius mutabilis and Lithobius crassipes differ in the frequency of feeding on lumbricid prey with the differences being associated with differences in body size. In the present study, the trophic separation of these two species was mainly due to bacterial marker FAs being high in L. crassipes and low in L. mutabilis , suggesting that L. crassipes is more strongly associated with the bacterial energy channel as compared to L. mutabilis .…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by molecular gut content analysis, lithobiids mainly prey on collembolans, lumbricids and Diptera larvae (Günther et al ). As indicated by FA composition, the former two predominantly feed on fungi/bacteria (Ruess et al ) and the latter on bacteria (Ferlian unpubl.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations